Analisis Pengelolaan Kegiatan Keagamaan Pasca Revitalisasi di Islamic Center Kota Prabumulih - Reva Alvira; Hasril Atieq Pohan; Emi Puspita Dewi (CV. ITTC INDONESIA, 2026)
This study aims to examine the perceptions of students from the Da’wah Management Study Program at UIN Raden Fatah Palembang toward the preaching (da’wah) delivered by Denis Lim. His preaching style is widely recognized as relaxed, communicative, and closely connected to younger audiences, making it an interesting subject of study from the perspective of da’wah students. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving students who have followed or are familiar with Denis Lim’s preaching. The results indicate that most students have a positive perception of his da’wah, particularly in terms of its clarity, simplicity of language, and ability to relate religious messages to everyday life. However, some students expressed critical views regarding the depth of the material and the tendency toward oversimplification. Overall, Denis Lim’s da’wah is perceived as effective in engaging younger audiences and has the potential to serve as a contemporary model of da’wah in the digital era.